ANALISIS RESPON PERMINTAAN KARET DI PROVINSI JAMBI - Yanita, Mirawati; Yazid, M.; Alamsyah, Zulkifli; Mulyana, Andy; Antoni, Mirza (Societa: Jurnal Ilmu-Ilmu Agribisnis, 2016)
This study aimed to analyze the factors that influence the demand for rubber, as well as to analyze demand response for rubber in Jambi Province. This research is using simultaneous equations through 3 Stage Least Square (3 SLS) estimation method. The result showed that factors influence the demand for rubber in Jambi is bokar prices, demand for rubber in South Sumatra, Indonesia rubber consumption, the price of synthetic rubber and rubber demand in Jambi at the prior period. While the response of demand for rubber in Jambi is inelastic as changing all the explanatory variables in the short term and long term.